China's 'New Normal': How will China's Growth Slowdown Affect Australia's Growth?. (10th July 2018) - Groenewold, Nicolaas
Abstract : China's 'New Normal' has been widely discussed in both the press and in academic circles. While many aspects of the Chinese economy are expected to change in this situation, an important component of the change is a significant and persistent growth slowdown. Not surprisingly, Australian commentary on China's growth slowdown has focussed on the implications for Australia's growth rate. Evaluations of this effect vary widely but are generally not firmly based on empirical research. This paper helps to fill this gap by analysing the likely effect on Australia's growth rate of a reduction in China's rate of economic growth. The analysis begins with a simple back‐of‐the‐envelope calculation and then moves to regression analysis and the simulation of a vector‐autoregressive model. Estimates are remarkably consistent across a range of models and suggest that the effect on Australia of a permanent fall in China's growth rate from 10% per annum to 7% per annum will be to reduce Australia's growth rate by about 0.2 percentage points in the short run and approximately 0.5 percentage points in the long run. While not trivial, given Australia's current growth rate, these estimates are hardly enough to justify prophesies of doom.